Interventional Radiology Locoregional Therapies for Intrahepatic Cholangiocarcinoma - Gregory Woodhead; Sean Lee; Lucas Struycken; Daniel Goldberg; Jack Hannallah; Shamar Young (Life, 2024)
Surgical resection remains the cornerstone of curative treatment for intrahepatic cholangiocarcinoma (iCCA), but this option is only available to a small percentage of patients. For patients with unresectable iCCA, systemic therapy with gemcitabine and platinum-based agents represents the mainstay of treatment; however, the armamentarium has grown to include targeted molecular therapies (e.g., FGFR2 inhibitors), use of adjuvant therapy, liver transplantation in select cases, immunotherapy, and locoregional liver-directed therapies. Despite advances, iCCA remains a challenge due to the advanced stage of many patients at diagnosis. Furthermore, given the improving options for systemic therapy and the fact that the majority of iCCA patients succumb to disease progression in the liver, the role of locoregional therapies has increased. This review will focus on the expanding role of interventional radiology and liver-directed therapies in the treatment of iCCA.